Seven strange & ghostly tales - Jacques, Brian (New York : Avon, 1993)
A collection of seven creepy stories.
Booklist.
Publisher's Weekly.
School Library Journal.
7.1.
7.1
5-8
Keywords: Ghosts -- Fiction; Short stories; Ghost stories; Short stories